The Roles of Event Organizers in Arranging Chinese-Indonesian Wedding Rituals - Clarence Finlay Limantara (Kata Kita: Journal of Language, Literature, and Teaching, 2020)
Nowadays, Chinese-Indonesians have already been modernized and many of them do not understand what rituals they have to undergo on their wedding day. It becomes a good opportunity for event organizers (EO) to do their businesses in arranging weddings. In this research, I am interested in finding out about the roles of event organizers in arranging Chinese-Indonesian wedding rituals. This study focuses on the roles of EO in running their business and arranging Chinese wedding rituals using the theory of consumerism. In consumerism, Chinese-Indonesian wedding rituals as a part of culture, can also be regarded as a product to be bought and sold. The data collected are from interviews with some EOs in Surabaya to find out the roles of EO in arranging Chinese-Indonesian wedding rituals. There are three different roles of EO, which are informant, organizer, and seller. Moreover, EO has the responsibility in succeeding the client’s wedding day.Keywords: Commodity, Consumerism, Event Organizer, Chinese-Indonesian, Wedding Ritual.